Efikasi Diri dan Prokrastinasi Akademik Saat Perkuliahan Daring pada Mahasiswa Organisatoris Ikatan Mahasiswa Muhammadiyah - Hesti Intan Sasongko Putri; Ghozali Rusyid Affandi (UNISBA Press, 2022)
Abstract. Students who are echoed in organizations have a series of task loads between academic assignments and organizational tasks. This research aims to find out the relationship between self-efficacy and academic procrastination during online learning on students who are members of the IMM organization. The hypothesis proposed in this study is that there is a negative relationship between self-efficacy and academic procrastination during online lectures on students who are members of the IMM organization. This study is a correlational quantitative study with 221 samples of students who are members of the IMM organization at . The measuring instruments used in the study used a scale of self-efficacy and a scale of academic procrastination. The data analysis used is the Pearson Product Moment correlation test. The results of the hypothesis test showed that there was a negative relationship between self-efficacy and academic procrastination during online lectures in students belonging to the IMM organization, with the results of correlation coefficient values showing r = -0.404 and values p = 0.000 < 0.01. In analysis specifically shows that it turns out that the highest aspect of correlation among other aspects is the level aspect (self-efficacy) with aspects of the time gap between plans and actual performance (academic procrastination) (r = -0.442 sig, 0.000<0.001). This shows that the more a person has confidence that he is able to complete various levels of tasks, then this will have an impact on increasing the ability to actualize plans in real form during online development. Abstrak. Mahasiswa yang tergabaung dalam organisasi memiliki beban tugas antara tugas akademik dan tugas organisasi. Penelitian ini bertujuan untuk mengetahui hubungan efikasi diri dengan prokrastinasi akademik saat perkuliahan daring pada mahasiswa yang mengikuti organisasi Ikatan Mahasiswa Muhammadiyah (IMM). Hipotesis penelitian ini adalah terdapat hubungan negatif antara efikasi diri dengan prokrastinasi akademik saat perkuliahan. Penelitian ini merupakan penelitian kuantitatif korelasional dengan 221 sampel mahasiswa. Alat ukur yang digunakan dalam penelitian ini menggunakan skala efikasi diri dan skala prokrastinasi akademik. Analisis data yang digunakan adalah Uji korelasi Pearson Product Moment. Hasil uji hipotesis menunjukkan terdapat hubungan negatif antara efikasi diri dengan prokrastinasi akademik saat perkuliahan daring pada mahasiswa yang tergabung dalam organisasi IMM, dengan hasil nilai koefisien korelasi menunjukkan r = -0,404 dan nilai p= 0,000 < 0,01. Aspek yang paling tinggi korelasinya adalah aspek tingkat level (efikasi diri) dengan aspek kesenjangan waktu antar rencana dan kinerja aktual (prokrastinasi akademik) (r = -0,442 sig, 0,000<0,001). Hal ini menunjukkan semakin seseorang memiliki keyakinan bahwa ia mampu menyelesaikan berbagai tingkatan tugas, maka hal ini akan berdampak pada peningkatan kemampuan dalam mengaktualisasikan rencana dalam bentuk nyata pada masa perkulihan daring.